Applying strength and conditioning practices to athletes with disability - Paulson, T.; Goosey-Tolfrey, V. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
The heterogeneity in impairment groups eligible for classification in the sarne sporting discipline presents a unique challenge for coaches and practitioners when considering benchmarks of physical performance (e.g. tetraplegia vs. cerebral palsy). As well as enhancing physical capacities, strength and conditioning-based interventions must also focus on maintaining athlete robustness and training availability whilst considering environmental influences on health and performance. The chapter will highlight considerations for the programming of interventions specific to the maintenance and enhancement of performance in athletes with a physical impairment. Where available, attention will be given to scientific literature that supports current practice. Unfortunately it is beyond the scope of this chapter to provide a comprehensive overview of considerations for supporting athletes with an intellectual, visual or hearing impairment. The basic principles of training programming and the expected adaptational responses to a training stimulus in these impairment groups remain largely consistent with AB practice. However, the communication of training requirements to athletes, the training environment in which an athlete is asked to operate and the supervision of individual sessions requires consideration on an athlete-to-athlete basis. More detailed information on supporting these athletes can be found elsewhere (Winnick and Porretta 2016).